Transport of Infrared Atmospheric Radiation : Fundamentals of the Greenhouse Phenomenon - Smirnov, Boris M. (Texts and Monographs in Theoretical Physics, 2020)
This book sets out to give a rigorous mathematical description of the greenhouse effect through the theory of infrared atmospheric emission. In contrast to traditional climatological analysis, this approach eschews empirical relations in favour of a strict thermodynamical derivation, based on data from NASA and from the HITRAN spectroscopy database. The results highlight new aspects of the role of clouds in the greenhouse effect.